A Review of Family Planning in India: Addressing Challenges and Priorities in India's Family Planning Program (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It's imperative that all components of India's family planning program be better coordinated,including planning, programs, monitoring and training. To be effective, family planning programs mustplace a high priority on high-quality treatment. India's family planning targets have yet to be met, despitethe country's best efforts. There is also a need for more male engagement, both as facilitators andbeneficiaries, and to address the sexual and reproductive issues of youth. The government must makesure that family planning is given top priority in the national development agenda. In order to attain theSustainable Development Goals, efforts must be taken to increase access to and raise the quality of familyplanning services.